2017
DOI: 10.1007/s00405-017-4734-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte ratio and red cell distribution width as prognostic factors for survival and recurrence in patients with oral cancer

Abstract: Although platelet to lymphocyte ratio (PLR) and red cell distribution width (RDW) have been reported as good predictors for survival outcomes in various cancers, there is limited data supporting these as reliable predictors in oral cancer. This study thus aimed to assess the prognostic value of PLR and RDW markers in predicting survival and recurrence rates in patients with oral cancer. The records of 374 oral cancer patients treated with curative intent over a 7-year period (2009-2015) were reviewed. Survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…Thrombocytosis may dampen the recognition and cytotoxicity of tumor cells by immune cells [28] or promote tumor growth by stimulating tumor angiogenesis, vascular invasion, and distant metastasis [32,33]. Our results reinforce the predictive values of PNI and PLR seen in previous retrospective studies, which showed that the PNI predicted overall survival and treatment-related toxicities in LAHNC patients [22,34] and that the PLR predicted survival outcomes and disease recurrence in HNC patients [35][36][37]. Moreover, this study demonstrated that the combination of these two parameters provided better prediction of one year mortality in LAHNC patients.…”
Section: Discussionsupporting
confidence: 86%
“…Thrombocytosis may dampen the recognition and cytotoxicity of tumor cells by immune cells [28] or promote tumor growth by stimulating tumor angiogenesis, vascular invasion, and distant metastasis [32,33]. Our results reinforce the predictive values of PNI and PLR seen in previous retrospective studies, which showed that the PNI predicted overall survival and treatment-related toxicities in LAHNC patients [22,34] and that the PLR predicted survival outcomes and disease recurrence in HNC patients [35][36][37]. Moreover, this study demonstrated that the combination of these two parameters provided better prediction of one year mortality in LAHNC patients.…”
Section: Discussionsupporting
confidence: 86%
“…When these confounding factors were excluded, RDW remained as an independent prognostic factor. However, Tangthongkum et al 17 have discussed the association of RDW with prognosis in Thailand OSCC patients, and they did not observe any prognostic value of RDW on survival outcome. One possibility for this discrepancy is the different RDW cutoff value.…”
Section: Discussionmentioning
confidence: 96%
“…One possibility for this discrepancy is the different RDW cutoff value. Tangthongkum et al 17 used the RDW cutoff point of 14.05, while the present study used the upper limited of the normal reference range of RDW (15.0). OSCC patients could be divided into totally different subgroup according to different RDW cutoff value, so it makes sense that the set of RDW cutoff value could affect the results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To our surprise, we also found that preoperative MCHC and RDW had an effect on the recurrence of patients with pancreatic cancer after surgery. RDW has been proven to be a marker of tumor recurrence in oral cancer [33]. To date, there are no studies regarding the relationship between MCHC and cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%